The Impact of Postnuptial Agreement on Husband and Wife's Ownership in Limited Liability Company - Kelly, Maria JF; Harjanto, Rudy; Widjojo, Anne Gunadi Martono (Global Legal Review, 2024)
Husband and wife who do not enter into a marriage agreement cannot establish a limited liability company with just the two of them, because in terms of ownership of assets, their assets constitute as one unit of joint property. Therefore the provision that a limited liability company is a capital association is not fulfilled. They then invite third parties, whether it's their own children or other third parties to become shareholders. Third parties like this are generally only invited to comply with statutory provisions and the number of shares they have in a company is usually also very small. The decision of the Constitutional Court number 69/PUU-XIII/2015 has an impact on many husbands and wives who are not also in mixed marriages to also make the marriage agreement. This study aims to see the impact of the shares owned by husband and wife if they then make a postnuptial agreement, whether the presence of a third party in the company still needed or not considering that between them there has been a separation of assets. The method used in this research is normative juridical. The result of this research is that if the husband and wife enter into a postnuptial agreement, then the participation of third parties is no longer necessary because they are already separate property owners, and shares previously owned by third parties can be transferred to one or both of them.